Bridging the gap between climate models and impact studies: the FORESEE Database. (5th February 2015) - Dobor, L.; Barcza, Z.; Hlásny, T.; Havasi, Á.; Horváth, F.; Ittzés, P.; Bartholy, J.
<x xml:space="preserve">Abstract</x> Studies on climate change impacts are essential for identifying vulnerabilities and developing adaptation options. However, such studies depend crucially on the availability of reliable climate data. In this study, we introduce the climatological database called FORESEE (Open Database for Climate Change Related Impact Studies in Central Europe), which was developed to support the research of and adaptation to climate change in Central and Eastern Europe: the region where knowledge of possible climate change effects is inadequate. A questionnaire‐based survey was used to specify database structure and content. FORESEE contains the seamless combination of gridded daily observation‐based data (1951–2013) built on the E‐OBS and CRU TS datasets, and a collection of climate projections (2014–2100). The future climate is represented by bias‐corrected meteorological data from 10 regional climate models (RCMs), driven by the A1B emission scenario. These latter data were developed within the frame of the ENSEMBLES FP6 project. Although FORESEE only covers a limited area of Central and Eastern Europe, the methodology of database development, the applied bias correction techniques, and the data dissemination method, can serve as a blueprint for similar initiatives.